Current and Voltage Harmonics Analysis in Green Building Case Study in Universitas Muhammadiyah Yogyakarta - Tony K. Hariadi; Agus Jamal; Nurohman Fadilah; Faaris Mujaahid (Journal of Electrical Technology UMY, 2020)
This paper described research to investigate Total Harmonic Distortion (THD) on a supposedly green building; Admission Building in Universitas Muhammadiyah Yogyakarta. Observation was done for seven days involving peak and non-peak hours including workdays and off days. Data sampling was recorded 24 hours with one-hour interval for primary parameter data including voltage, current, power factor and frequency on each phase in three phases system. Secondary data calculated to find voltage and current THD and finally to evaluate the loss of money due to power loss as the result of harmonic and unbalance load. Investigation indicated that the building has not met the IEEE 512-2014 standard for Total Harmonic Distortion. National electricity company, PLN (Perusahaan Listrik Negara) as Government Company, has made regulation about tariff and standard. Electricity tariff in Indonesia has been divided into categories based on user, commercial, social, or housing. Based on this tariff, loss of cost was calculated. Cost due to electricity loss in the building was not high since the building has good electricity installation as green building. Total Harmonic distortion reduction was recommended using single tune order 5 filter.